Association of Single Nucleotide Polymorphisms in CYP1B1 and COMT Genes with Breast Cancer Susceptibility in Indian Women. Issue 5 (2nd June 2013) - Yadav, Sharawan; Singhal, Naveen Kumar; Singh, Virendra; Rastogi, Neeraj; Srivastava, Pramod Kumar; Singh, Mahendra Pratap
Abstract : Cytochrome P450 1B1 (CYP1B1) and catechol-$O$-methyltransferase (COMT) enzymes play critical roles in estrogen metabolism. Alterations in the catalytic activity of CYP1B1 and COMT enzymes have been found associated with altered breast cancer risk in postmenopausal women in many populations. The substitution of leucine (Leu) to valine (Val) at codon 432 increases the catalytic activity of CYP1B1, however, substitution of Val to methionine (Met) at codon 158 decreases the catalytic activity of COMT. The present study was performed to evaluate the associations of CYP1B1 Leu 432 Val and/or COMT Val 158 Met polymorphisms with total, premenopausal and postmenopausal breast cancer risks in Indian women. COMT and CYP1B1 polymorphisms in controls and breast cancer patients were analyzed employing polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) followed by gel electrophoresis. Although CYP1B1 and COMT genotypes did not exhibit statistically significant association with breast cancer risks when analyzed individually, COMT wild type (Val 158 Val) in combination with CYP1B1 heterozygous variant (Leu 432 Val) [OR: 0.21; 95% CI (0.05–0.82), p value; 0.021] and COMT heterozygous variant (Val 158 Met) in combination with CYP1B1 wild type (Leu 432 Leu) [OR: 0.29; 95% CI (0.08–0.96), p value; 0.042] showed significant protective association with premenopausal breast cancer risk. The results demonstrate that CYP1B1 wild type in combination with COMT heterozygous or their inverse combination offer protection against breast cancer in premenopausal Indian women.